Working with Cultural Heritage from the Local Environment: Analysis of Perceptions of Future Teachers - Patricia Suárez-Álvarez; Alejandro Otero-Varela (Social Sciences)
Cultural heritage refers to the set of tangible and intangible assets that a society inherits from its ancestors and transmits to future generations. The training of future teachers in this subject is vital, as they will be responsible for using resources and developing activities that promote the appreciation and conservation of cultural heritage by society. In this article, we conducted research among pre-service teachers at the University of Córdoba (Spain). Our goal was to explore, using primary sources, the conceptions that future teachers had about the cultural heritage of their local environment and to identify any difficulties students may have in recognizing and valuing it, as well as to promote critical thinking when addressing key concepts such as identity/otherness. We conducted a study among 189 students completing Early Childhood and Primary Education degrees which allowed us to draw conclusions about the identification, conception, and appreciation of heritage. These results will serve as a starting point for reflecting on their needs in this regard, with the aim of implementing future didactic improvements.